The IMPLEMENTATION OF THE INCREMENTAL METHOD IN WEB BASED ARCHIVES MANAGEMENT SYSTEM: IMPLEMENTASI METODE INCREMENTAL PADA SISTEM PENGELOLAAN ARSIP BERBASIS WEB - Surya Ade Saputera; Sri Handayani; Eki Sawaludin (JTIS: Journal of Technopreneurship and Information System, 2023)
The incremental method is an approach in software development in which the system is developed in stages by adding new features gradually. In the context of web-based archive management, the implementation of the incremental method can bring a number of significant benefits. The purpose of this research is to implement the incremental method on a web-based records management system in a particular organization or entity. This research aims to increase the efficiency and flexibility of system development, as well as reduce the risk of errors and project failures. In this study, an analysis of the needs of web-based records management for the organization was first carried out. After that, the records management system to be developed is planned based on the most important and critical features. Then, system development begins by adding these features in the early stages. It is hoped that the implementation of the incremental method on a web-based records management system will bring a number of benefits. Key features are immediately usable by users, helping to increase efficiency and productivity. In the long term, the records management system can be developed as a whole and continuously with this method, accommodating the changing needs of users and organizations. Keywords: incremental method, archive management system, software development, efficiency, flexibility